QUALITATIVE EXPLORATION OF SOCIAL FACTORS THAT UNDERLY MOTIVATIONS OF MEDICAL STUDENTS TO ASPIRE TO THE PROFESSION (Proceedings of the International Conference on Education, 2021)
Aspiring physicians’ motivational discourses have mostly delineated intrinsic versus extrinsic factors in the literature, lacking further comprehension of factors underpinning such decision. The purpose of this qualitative study is to deepen the understanding of factors and motivations that lead students to aspire to the medical profession.Semi-structured interviews were applied to 55 medical students from 3 Universities in Mexico, transcriptions were submitted to iterative rounds of coding for analysis using grounded theory. Predominant reasons to enter the profession were: I) Interest in the medical science, II) Aspiring to honorability and status, III) Having a physician family member, IV) Personal experience with illness and V) Desire to help (altruism). Beyond discourse, one striking finding was that most chose their career lacking conscious reasoning and autonomy either because a)ideation/decision was conceived during childhood, b) lacked clear motivation arguments and c)had significant external influence (particularly from parents) on their choice. Such findings helped develop a model that recognizes factors that underly the conscious motivations that students exhibit including: 1) Parental desire/pressure. 2) Proximity of family medical models and lack of exposure to other disciplines. 3) Idealization of the doctor figure during childhood. 4) Influence of television programs. 5) The notion that the career ensures future economic stability/prosperity. 6) Desire of social mobility. The prior socialization of students conditions an aspiration based on a perception of heightened professional status of the medical profession that may differ from the current context. The motivations have an extrinsic preponderance and do not reflect autonomy and adequate understanding of the implications of studying medicine and the future practice of the profession. This can generate problems about their own satisfaction and identity and with respect to the social impact in the exercise of their future role.
Keywords: motivations; medical students; medical profession; medical education; socialization